THE DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA USING KODULAR IN BIOLOGY FOR GRADE VII STUDENTS AT PUBLIC JUNIOR HIGH SCHOOL 5 TAEBENU SATAP - Aranci Amheka; Khatrin J. Takuneno; Yonly A. Benufinit (Journal of Innovative Technologies in Learning and Education, 2024)
The purpose of this study is to create an android-based learning media using Kodular for junior high school grade VII biology in Public Junior 5 Taebenu SATAP. The research took a quasi-experimental form, which then compared the efficacy of the media developed for traditional teaching methods in regard to enhancing student understanding of complex biological concepts. Significant improvements were shown in the post-test scores, engagement, and motivation for the first half of this experimental group by using Android-based learning media as compared to control group. The outcome surfaced that more interactive and multimedia-intensive user interface of mobile application provided significant influence on the level of understanding students had about abstract biological concepts, which consequently contribute to better learning results. While rural schools may lack the resources that such challenges demand, this study demonstrates the potentially revolutionary way that mobile learning tools can address science education. The results indicate that utilizing Android-supported applications in the classroom is a practical way to create individualized, engaging learning opportunities for learners of the 21st century